An Analysis of Students’ Perceptions on Google Classroom Media Used By English Teachers during Pandemic Covid-19 - Riswanto Riswanto (Unib Press, 2022)
Online learning or virtual classrooms use technology to help students and teachers with distance learning, with teachers providing accessible teaching materials. The purpose of this study is to describe students' perceived convenience and usefulness of Google Classroom material. This was a quantitative research that used a Likert Scale questionnaire. This study focuses on XI IPS students at SMAN 8 Bengkulu. To estimate the proportion of students' scores, data was analyzed using Sudjana's provided algorithm. The results suggest that around 79 percent, or more than half of the students, find it easy to study by utilizing Google Classroom since it offers an easy operating system and features that are simple to comprehend. Overall, based on the result of the research, there was more than half of the total demonstrated positive perceptions.